Repositioning of the South African Communist Party (SACP) in the politics of post-apartheid South Africa : a critical study of SACP from 1990-2010 - Mthembi, Phillip (University of Limpopo, 2014)
The study was about the South African Communist Party (SACP) and its entry into SA politics after 1990. The main question is whether it should contest elections independently of its Tripartite alliance partners led by ANC in democratic SA. As a democratic country it allows any party to participate in the elections. Given that space SACP can contest and triumph electorally thus assume the reins of government. For SA to become socialist, SACP has to campaign and triumph electorally for this to happen. The study followed a qualitative research paradigm. Purposeful sampling was used to collect data through in-depth interviews with information-rich respondents who have specialist knowledge about the study. Interviews and document analysis were used for data collection. For this reason, open-ended questions in the form of an interview guide were used to solicit information, perceptions and attitudes towards and about SACP. A tape recorder was used to capture information from these interviews. The recorded data was transcribed and coded into themes one by one which in turn formed part of the research portfolio. From the study findings contemporary SACP is a product of the revisionism that has come to characterise the post-Cold War. It is not surprising why the party then is not ready to contest election alone.
Thesis (M.A. (Political Science)) -- University of Limpopo, 2014
Keywords: Politics; South African Communist Party; Post-apartheid era; Politics; Communist parties; Political parties - Congresses; Post-apartheid era -- South Africa; South Africa -- Politics and government -- 1990-2010